La transdisciplinareidad del conocimiento científico contemporáneo. - Fernando González-Cuevas, Manuel (Quaestiones Disputatae)
Reflection on methodology and knowledge, as the object of scientific inquiry, have permeated knowledge since Greek antiquity, since they have questioned variables, aspects, approaches and trends within the research process on phenomena, environments, as well as the reality of the subject (human), generating a methodological outline and appropriation of knowledge. This statement allows understanding a parallel between the process of inquiry with the object, called knowledge, which is divided into two major meanings relevant to this dissertation; on the one hand, the methodical approaches emanating from classical science and on the other side the processes constituted from the complexity, which disregard the reductionist paradigms to link the transdisciplinary members of contemporary knowledge.